2015
DOI: 10.1590/1516-1439.005715
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Gold Adsorption from Chloride Media

Abstract: In this paper, adsorption of gold from chloride media using commercial sorbent ) and biomass residue (rice hull (RH)) were investigated. The different adsorption parameters, sorbent dosage, contact time, temperature and pH of solution on adsorption (%) were studied in detail on a batch sorption. Before the RH was activated, adsorption (%) was poor compared with L-214. However, after the RH was activated at 1000 °C under an argon atmosphere, the gold adsorption (%) increased four-fold. X-ray fluorescence (XRF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…As for Langmuir isotherm, higher Q max and larger b are desirable to design an effective uptake process, and these two parameters rose from 252.98 to 358.69 mg/g, 0.02132 to 0.1208 L/mg, respectively, when incubation temperature changed from 20 to 50°C. Thus, it suggested that higher temperature favored the uptake of gold ions onto the P. sanguineus biomass and the uptake process was endothermic, which was consistent with the results of several other reports studying gold adsorption behavior …”
Section: Resultssupporting
confidence: 90%
“…As for Langmuir isotherm, higher Q max and larger b are desirable to design an effective uptake process, and these two parameters rose from 252.98 to 358.69 mg/g, 0.02132 to 0.1208 L/mg, respectively, when incubation temperature changed from 20 to 50°C. Thus, it suggested that higher temperature favored the uptake of gold ions onto the P. sanguineus biomass and the uptake process was endothermic, which was consistent with the results of several other reports studying gold adsorption behavior …”
Section: Resultssupporting
confidence: 90%
“…51,52 The high affinity of the carbonaceous surface of CSCs for Au(III) is therefore likely to be due to the high standard electrode potential of the [AuCl 4 ] À1 /Au 0 couple, E [AuCl 4 ] À1 /Au 0 ¼ 1.00 V, and the similarly high reduction potential, E [AuCl 4 ] À1 /[AuCl 2 ] À1 ¼ 0.93 V for the reduction to Au 1+ , via this reduction-adsorption mechanism. 18,25,[51][52][53][54][55] This mechanism allows for the creation of vacancies on the surface of the material as the reduced species deposits, which leads to higher uptake of the metal from solution and increased adsorption capacity of the adsorbate surface.…”
Section: Mechanism Of Gold Adsorptionmentioning
confidence: 99%
“…Several studies have focussed on the development of adsorbents for the recovery or removal of Au 3+ species from aqueous waste streams. 3,54,[61][62][63][64][65][66][67] Table 6 demonstrates the range of biobased materials being developed for gold recovery. It can be observed that CSC500 materials demonstrate excellent performance with an adsorption capacity of 320 mg g À1 .…”
Section: Gold Adsorption Isothermsmentioning
confidence: 99%
“…In addition, the adsorbents should have particle sizes suitable for use in fixed bed systems, avoiding pressure drop and column clogging, and should have also good chemical stability in strong acidic solutions, considering this is the condition of typical gold-bearing liquors [18]. Various adsorbents have been investigated for gold recovery, including commercial resins [19,20], crosslinked polyethyleneimine resin [19], and a wide range of natural-derived adsorbents such as polyethylenimine modified Ca 2+ -alginate fibres [18], polyethylenimine modified Lagerstroemia speciosa leaves [21], banana peel derivatives [22], raw date pits [23], and tannin-derived materials [6,[24][25][26]. The successful uptake of gold has been explained by electrostatic interaction between the gold complexes in solution and the adsorbent surface, followed by a reduction mechanism, involving amine, hydroxyl, and aldehyde groups of the adsorbents [18,21,27,28].…”
Section: Introductionmentioning
confidence: 99%